2023
DOI: 10.1021/jacs.3c05052
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonally Engineered Albumin with Attenuated Macrophage Phagocytosis for the Targeted Visualization and Phototherapy of Liver Cancer

Abstract: The five-year survival rate of hepatocellular carcinoma (HCC) remains unsatisfactory. This reflects, in part, the paucity of effective methods that allow the target-specific diagnosis and therapy of HCC. Here, we report a strategy based on engineered human serum albumin (HSA) that permits the HCC-targeted delivery of diagnostic and therapeutic agents. Covalent cysteine conjugation combined with the exploitation of host−guest chemistry was used to effect the orthogonal functionalization of HSA with two function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
(71 reference statements)
0
2
0
1
Order By: Relevance
“…作为发生率和病死率均较高的恶性肿瘤 [ 42 ] ,肝癌的早筛、早诊极为重要。长期以来,血清学标志物AFP因其具有样本易获得、创伤小、可重复等特点已广泛应用于肝癌的筛查和预警 [ 43 - 45 ] 。1956年,AFP在人胎儿血清中首次发现 [ 46 ] 。从妊娠第四周开始,由于胎儿肝脏等器官的分泌,AFP水平持续升高 [ 47 ] ,待胎儿出生后则持续下降并维持在极低水平,但在肝癌发生时其水平又会异常上升。有研究认为,肝癌患者血清AFP水平升高与位于人类4号染色体长臂上的相关基因有关,该基因上的独立增强子抑制的阻断和沉默子的缺失导致启动子的活性恢复,最终使得AFP过表达 [ 1 , 48 ] 。也有研究证明,AFP可以通过启动环AMP-蛋白激酶A途径、钙离子内流和caspase-3介导的凋亡信号促进肿瘤增殖 [ 49 - 51 ] 。但是,临床上有约30%的AFP阴性肝癌患者,且其特异度较低,所以目前AFP用于诊断肝癌饱受争议 [ 52 ] 。目前研究显示,PIVKA-Ⅱ诊断肝癌的效能高于AFP,有着较高的敏感度和特异度 [ 5 ] 。PIVKA-Ⅱ可通过增强细胞增殖、肿瘤血管生成等方式促进肿瘤的增殖和转移 [ 53 ] 。目前,PIVKA-Ⅱ在肝癌中过表达的机制尚无定论,肝癌中PIVKA-Ⅱ过表达可能与缺氧微环境、维生素K代谢受损及凝血酶原前体过表达相关。但是,PIVKA-Ⅱ水平不仅在肝癌患者血清中升高,在维生素K缺乏症及服用维生素K拮抗剂患者的血液中也会异常升高,这也使得PIVKA-Ⅱ在诊断肝癌时存在一定局限 [ 54 ] 。GPC-3是GPC家族一员,在正常肝脏组织中几乎不表达,但其在肝癌组织中的阳性率高达90%。其通过Wnt/β-catenin信号通路参与肝癌的发生、增殖和转移,是肝癌的重要血清标志物之一 [ 55 ] 。…”
Section: 讨论unclassified
“…作为发生率和病死率均较高的恶性肿瘤 [ 42 ] ,肝癌的早筛、早诊极为重要。长期以来,血清学标志物AFP因其具有样本易获得、创伤小、可重复等特点已广泛应用于肝癌的筛查和预警 [ 43 - 45 ] 。1956年,AFP在人胎儿血清中首次发现 [ 46 ] 。从妊娠第四周开始,由于胎儿肝脏等器官的分泌,AFP水平持续升高 [ 47 ] ,待胎儿出生后则持续下降并维持在极低水平,但在肝癌发生时其水平又会异常上升。有研究认为,肝癌患者血清AFP水平升高与位于人类4号染色体长臂上的相关基因有关,该基因上的独立增强子抑制的阻断和沉默子的缺失导致启动子的活性恢复,最终使得AFP过表达 [ 1 , 48 ] 。也有研究证明,AFP可以通过启动环AMP-蛋白激酶A途径、钙离子内流和caspase-3介导的凋亡信号促进肿瘤增殖 [ 49 - 51 ] 。但是,临床上有约30%的AFP阴性肝癌患者,且其特异度较低,所以目前AFP用于诊断肝癌饱受争议 [ 52 ] 。目前研究显示,PIVKA-Ⅱ诊断肝癌的效能高于AFP,有着较高的敏感度和特异度 [ 5 ] 。PIVKA-Ⅱ可通过增强细胞增殖、肿瘤血管生成等方式促进肿瘤的增殖和转移 [ 53 ] 。目前,PIVKA-Ⅱ在肝癌中过表达的机制尚无定论,肝癌中PIVKA-Ⅱ过表达可能与缺氧微环境、维生素K代谢受损及凝血酶原前体过表达相关。但是,PIVKA-Ⅱ水平不仅在肝癌患者血清中升高,在维生素K缺乏症及服用维生素K拮抗剂患者的血液中也会异常升高,这也使得PIVKA-Ⅱ在诊断肝癌时存在一定局限 [ 54 ] 。GPC-3是GPC家族一员,在正常肝脏组织中几乎不表达,但其在肝癌组织中的阳性率高达90%。其通过Wnt/β-catenin信号通路参与肝癌的发生、增殖和转移,是肝癌的重要血清标志物之一 [ 55 ] 。…”
Section: 讨论unclassified
“…25–27 All these potential advantages make the detection method based on fluorescent probes a hot area of research for development. 28–37 In general, fluorescent probes respond to target analytes based on specific interactions to generate changes in fluorescence intensity. 38–44 However, detection methods based on emission intensities at a single wavelength are not reliable and accurate enough due to the interference from the environment and probe concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the small-molecular fluorescent probes developed for HSA can be categorized into noncovalent and covalent binding modes. , It has been suggested that covalent binding exhibits better selectivity and stability to resist interference from small biomolecules and drugs. ,,, Ajayaghosh et al developed self-assembling dyes that form nonfluorescent nanoparticles, and HSA can selectively disassemble and covalently bind to generate a fluorescent response . He et al orthogonally functionalized HSA using covalent and supramolecular approaches to modular peptides, achieving specific optical visualization and photodynamic ablation of malignant liver tumors of human origin . However, the fluorescent probes reported for recognizing intracellular HSA were limited in their function for sensing or imaging, while the consumption of HSA after covalent binding would possibly disrupt the redox homeostasis and exacerbate the pathological state. Therefore, being able to image HSA under oxidative stress and simultaneously release antioxidant drugs to counteract oxidative stress and maintain redox homeostasis will be significant for disease diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%